Disgust and Contamination: A Cross-National Comparison of Ghana and the United States - Skolnick, Alexander J.; Dzokoto, Vivian A. (Frontiers in Psychology, 2013)
The emotion of disgust, with feelings of revulsion and behavioral withdrawal, make it a prime emotion to aid in the avoidance of sources of contamination, including sources of potential infectious disease. We tested the theory that living in a region with a historically high prevalence of infectious diseases would promote higher levels of disgust and contamination sensitivity as a protective measure. A sample of undergraduates from Ghana (n = 103, 57 women), a country with a historically high prevalence of infectious diseases, showed significantly higher scores on scales assessing disgust, contamination, and disease susceptibility than a sample of undergraduates from the United States (n = 96, 58 women), a country with lower levels of disease threat. Contamination sensitivity mediated the national differences in disgust. Disgust connoting contamination also produced larger cross-national effect sizes than other types of disgust. Finally, a factor analysis on the Ghanaian responses to one of the disgust scales did not resemble the usual three-factor solution found in West. Taken together, the results were consistent with the hypothesis that a region with a higher prevalence of infectious disease threats would produce greater sensitivity to disgust and contamination than seen in lower disease threat regions. This first study on disgust in Africa showed that disgust sensitivity could differ considerably from that in the West.